Calligraphic of contemporary Malay world: the case of Selangor mosques - Baniyamin, Nurhaya; Kamaruddin, Zumahiran; Abdul Razak, Rajabi (2019)
Patterning and Geometries of Malay Interior Architecture Modern Mosques in the Malay world is primarily, a symbol of Islamic architecture of the highest quality and aesthetic value. Islamic art has been constantly infused in Malay regional architecture thru motifs and ornamentation. The three different motifs, are namely floral, geometry and calligraphy configured to convey abstract meanings of Islamic teachings to the viewers, embodying the messages of Allah the Almighty or the sayings of the prophets to the congregations. Mosques in the Malay region is now synonymous with Arabic alphabet characters, verses from the Quran, religious phrase, Islamic quotes, poems and local Arabic writing called Jawi were among the common elements depicted as calligraphic decorative components. The usage and application of the various decorative Arabic scripts concerning art and design is part of a study in identifying and describing major Islamic calligraphic themes, styles and scripts. The study analyzes the styles of Islamic calligraphy particularly used in a mosque (interior and exterior settings), with focus on sites in Selangor. It was found that there is a range of combination of calligraphy with other motifs, the traits of scripts in the mosque and their decorative mediums and techniques. Sites surveyed include observation of selected contemporary mosques as well as interview of experts including imams and mosque management. The selected mosques reveal different calligraphic decorative component. The results indicated that the aesthetic values, function and appropriate location elevate the mosque in reflecting the superiority of Allah the Almighty. The study reveals the depth of relationship between Malay community in Islam and the beauty of the calligraphy in various mediums of expression including plaster, ceramic tiles, woodwork, metalwork, and glass-based products with exclusive plus distinctive features.